Energy absorption of metallic and composite tubes - Lee, Yong Kuang (2017)
Optimising energy absorber has always been a research focus for many industries, for instance like automotive industry to improve crashworthiness and reduce fatality. Thin walled tubes are widely used as energy absorber as it is easy to manufacture, widely available and cost effective. Many studies focused on determining the most efficient energy absorber by using circular thin walled tubes and increasing number of layers of carbon fibre reinforced polymer (CFRP) or orienting the angles of CFRP layers. However other studies have shown that other geometries can outperform circular thin walled tubes. Therefore this study aims to compare different geometries (circular and square thin walled tubes) at different layers of CFRP under both axial and lateral loading conditions. The general trend observed is the total energy absorption and SEA increases for both geometries as the number of layers of CFRP increases. Results have shown that square geometries have promising performance in both total energy absorbed and specific energy absorption (SEA) as opposed to its circular counterpart. For lateral loading, crucial parameters like the critical displacement is observed to affect the specimen’s energy absorption capability greatly. However, a different trend is observed for both geometries upon the addition of CFRP layers, which will arrive at a different conclusion for the most effective energy absorber at higher number of CFRP layers.